Landscape of Noncoding RNA in Prostate Cancer. Issue 11 (November 2019) - Hua, Junjie T.; Chen, Sujun; He, Housheng H.
Abstract : The transcriptome of prostate cancer is highly heterogeneous, with noncoding transcripts being essential players. Long noncoding RNAs (lncRNAs) and circular RNAs (circRNAs) are two unique classes of noncoding RNA drawing increasing attention. Biologically, they have intriguing properties with important regulatory functions. Clinically, they present as promising biomarkers and therapeutic targets. Recent advancements in technologies have opened up new directions for noncoding RNA research, which include RNA–protein interaction, RNA secondary structure, and spatial transcriptomics. Furthermore, recent work has also evaluated the clinical applications of these noncoding RNAs in noninvasive liquid biopsy and RNA-based therapies. In this review, we summarize recent findings on lncRNAs and circRNAs in prostate cancer, discuss their clinical utilities, and highlight these exciting areas of research. Highlights: Long noncoding RNA (lncRNA) and circular RNA (circRNA) are pervasive noncoding RNA classes with important functional roles, and are frequently dysregulated in prostate cancer. While circRNAs share similarities with lncRNAs, the circular conformation leads to novel functional mechanisms, increased stability and unique clinical applications. Recent technological advancements impel noncoding (nc)RNA research in RNA–protein interaction, RNA secondary structure, and spatial transcriptomics, which may reveal novel findings for clinical translation. Both lncRNAs and circRNAs are promising biomarkers due to their expression specificity, and may be exploited for noninvasive liquid biopsy applications. RNAi and antisense oligonucleotides (ASOs) are therapeutic strategies for targeting oncogenic ncRNAs, and can be delivered through nanoparticles or conjugated antibodies or receptors.